Reduced ovarian reserve in young early breast cancer patients: Preliminary data from a prospective cohort trial - Wenners, Antonia; Grambach, Jana; Koss, Juliane; Maass, Nicolai; Jonat, Walter; Schmutzler, Andreas; Mundhenke, Christoph (BMC Cancer, 2017)
Background: The numerous side effects of chemotherapy in patients with breast cancer are well known. However, the precise effects of chemotherapy on ovarian function in premenopausal women are poorly investigated. The patients are at risk of developing sexual hormone deficiency and impaired fertility. This prospective cohort study addresses predictive parameters of ovarian reserve after chemotherapy. Methods: Fifty-one premenopausal women (28-46years) with primary breast cancer were included in the trial. All of them received anthracycline-based chemotherapy (n=18), or combinations with taxanes (n=30), or anthracycline-free chemotherapy (n=3). Changes in hormone levels (LH, FSH, E2 and Anti-Müllerian hormone (AMH)), antral follicle count (AFC), and amenorrhea were determined before (V1), and 6, 12 and 24months after the initiation of chemotherapy (V2-V4). Quality of life parameters were evaluated. The additional impact of parity, BMI, and smoking on ovarian reserve was also assessed. Results: AFC and AMH fell very markedly after chemotherapy and did not return to pre-treatment levels until V4. A significant positive correlation was noted in AFC before and 1year after chemotherapy. AMH levels at V2-V4 were significantly correlated with those registered at V1. AFC and AMH were negatively correlated with age. Continued smoking had a significant detrimental effect on AFC after 24months. LH and FSH levels increased between V1 and V2 and fell at V3 and V4, but stayed above pre-chemotherapy values. Two years after the start of chemotherapy 31/51 patients were amenorrhoic while 17 resumed their menstrual cycle this was not influenced by the type of chemotherapy or age. Non-smokers were 13 times more likely to resume their menstruation than smokers. Quality of life (QL) was significantly lower 6months after the initiation of chemotherapy. QL at one and 2years after chemotherapy did not differ significantly from pre-chemotherapy scores. Conclusions: Our study contributes to a better understanding and prediction of ovarian reserve in young early breast cancer patients undergoing chemotherapy. The data suggest that personal counseling in regard of the preservation of fertility should be offered especially to patients of a higher age, with low AMH levels or low follicle counts. Patients should be advised to stop smoking in order to enhance the likelihood of preserving their fertility.
CRIS-Team Scopus Importer:2022-11-17
Keywords: AMH; Breast cancer; Fertility preservation; Ovarian reserve